Budget deficit (Henry Stewart Talks, 2026)
Budget deficit definition, Government spending vs revenue, Causes of deficits, Impact on national debt & debt-to-GDP, Fiscal sustainability & investor trust, Debt management options & trade-offs, Borrowed funds in economic growth